Northrop Frye on Canada - Frye, Northrop (Book collections on Project MUSE., 2003)
Brings together all of the writings of Northrop Frye, both published and unpublished, on the subject of Canadian literature and culture, from his early book reviews of the 1930s and 1940s through his cultural commentaries of the 60s, 70s, and 80s.